Efficacy of Sodium Tripolyphosphate and Non-Phosphate Additives on the survival of Vibrio parahaemolyticus on Prawns (Fenneropenaeus indicus) (H. Milne-Edwards, 1837) during Frozen Storage - Bini, Francis; Sudha, Santha; Hatha, A. M. (Fishery Technology, 2017)
Use of sodium tripolyphosphate (STPP) and nonphosphate additives (NP1) in combination with sodium chloride is practised in soaking to prevent drip loss while thawing the frozen shrimp. In the present study, we have determined the efficacy of these additives on the survival of Vibrio parahaemolyticus on prawns (Fenneropenaeus indicus), during block freezing and individual quick freezing conditions. Freshly harvested prawns were beheaded and treated with a blend solution containing STPP/NP1 at 3 g 100 ml-1 in combination with sodium chloride at 2g 100 ml-1, in two separate experiments. At appropriate time intervals, whole prawns were sampled and dilutions plated onto TCBS agar medium to determine the number of V. parahaemolyticus. Experiments were performed in triplicate. Results indicated that STPP treated samples exhibited significant (p<0.05) reduction in the number of V. parahaemolyticus at any given time in both frozen conditions over the course of storage period as compared with non- phosphate treated samples. On the other hand, control samples (water dip) showed a gradual reduction in the number of organism, which is attributed to freezing. Therefore, sodium tripolyphosphate can be used as a promising drip loss preventer as well as an antimicrobial, to enhance the safety of frozen seafood.